Interview with Shailesh Prabhu, Indian Game Designer - Prabhu, Shailesh (Game Studies, 2016)
Interview with the Indian Game Designer Shailesh Prabhu about his game Sky Sutra.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé